High Efficacy of Rose Bengal in Reducing the Pathogenicity of Escherichia coli Isolated From Diarrheal Infections - Christ Dieuveil Bayakissa Malanda; Christian Aimé Kayath; Nicole Prisca Makaya Dangui Nieko; Frédéric Yannick Okouakoua; Ndelani Nkalla Lambi; Dieuvit Haïdide Kibamba Niangui; Sergy Patrick Junior Bissoko; Duchel Jeandevi Kinouani Kinavouidi (International Journal of Microbiology, 2025)
Diarrheal infections, a leading cause of global morbidity and mortality, are frequently attributed to pathogenic Escherichia coli strains. The rise of antibiotic resistance among these pathogens necessitates the exploration of alternative therapeutic agents. This study is aimed at evaluating the Rose Bengal effect to fight antibiotic resistance in pathogenic E. coli. Using a combination of in vitro assays—including microbiological isolation, 16S RNA molecular identification, acid resistance testing, biofilm and swarming assays, hemolytic activity evaluation, and antibiograms—and in vivo analysis with Rhynchophorus phoenicis larvae, 22 E. coli isolates were obtained. Molecular analyses identified four pathogenic strains: KNH8 (PQ864811), KNH11 (PQ864812), KNH14 (PQ864813), and KNH16 (PQ864814), classified as enterotoxigenic E. coli (ETEC) and enteropathogenic E. coli (EPEC). Pathogenicity assessments revealed that Rose Bengal (200 μM) significantly reduced acid and bile salt resistance, biofilm formation, swarming motility, and hemolytic activity in all strains. Furthermore, Rose Bengal enhanced the sensitivity of these strains to five antibiotics—imipenem, kanamycin, chloramphenicol, gentamicin, and amoxicillin/clavulanic acid (AMC)—with increases ranging from twofold to sixfold in pathogenic strains (KNH8, KNH11, KNH14, and KNH16). These effects were further corroborated by in vivo testing using R. phoenicis larvae. The findings highlight the virulent potential of these E. coli strains and suggest Rose Bengal as a promising antimicrobial agent against multidrug-resistant pathogens.